HUBUNGAN TINGKAT KINERJA PETUGAS DENGAN KEPUASAN PASIEN DI PUSKESMAS MASBAGIK - Baiq Weni Wardani; Fatriyawan, Abdul Aziz (Nusadaya Journal of Multidiciplinary Studies, 2022)
Masbagik Health Center has a good performance, but that does not mean that it has never experienced problems in serving the patients. This study aims to determine the description and influence of the performance of officers at the Masbagik Health Center, East Lombok in 2022. This research uses analytical descriptive research. Data collection was carried out by referring to the questionnaire sheet with a sample of 100 outpatients, the data analysis used was univariate and bivariate analysis. The percentage results obtained that most of the respondents answered good performance of 97 people (97.0%). It is known that respondents who are dissatisfied are 2 people with 3 answer points, a score of 1 is 1 answer and a score of 2 is 2 answers (0.3%). The better the performance of the officers, the higher the value of patient satisfaction.